Is Alteration of Magnetite During Rock Weathering Climate‐Dependent?. Issue 10 (8th October 2021) - Zhang, Qi; Appel, Erwin; Basavaiah, Nathani; Hu, Shouyun; Zhu, Xiuhua; Neumann, Udo
Abstract: Magnetic records in sedimentary sequences are often used as paleoclimate proxies. Climate‐specific alteration of magnetite during rock weathering in the catchment might contribute to proxy variations in sediment sinks. In an actualistic study, we investigated the effects of magnetite alteration using weathered pebble material on basaltic parent rock. We collected samples from the Deccan basalts (India) across a large difference of mean annual precipitation (MAP; ∼800–3, 200 mm), and also from the Emeishan basalts (SW‐China) to compare alteration effects at similar MAP (∼1, 100 mm) but ∼12°C–15°C lower mean annual temperature (MAT). We used rocks with lamellar magnetite‐ilmenite texture to ensure the best possible uniform parent rock magnetic mineralogy. We separated the weathered material into five groups by grain size, assuming that alteration increases in finer pebbles. Only magnetic susceptibility ( χ ) shows a systematic change, with an increase that is weakly stronger for higher MAP. Consistent with a simplified model, the χ ‐increase may represent progressive maghemitization. For the Emeishan basalts, we found a significantly stronger degree of alteration, including loss of magnetite. We explain this effect, which is surprising regarding the clearly lower MAT, by frost‐induced micro‐cracks due to physical weathering that opens pathways for oxygen and humidity into particle interiors. Based on these findings, we conclude that climate‐related alteration effects of magnetite during rock weathering are in most cases outweighed by parent rock heterogeneity, and magnetic proxy records in derived sediment archives are unlikely to record climate‐related magnetite alteration acquired during rock weathering, at least for catchment with basalts. Plain Language Summary: Magnetite is of primary importance for magnetic records in paleoclimate archives such as lake sediments. Source material for archives derives from bedrock weathering. Possible climate‐dependent alteration of magnetite during rock weathering may be an important factor controlling proxy variations. Previous results from lacustrine sediments indicated a relationship with humidity conditions in the catchment. To rate how significant such weathering effects are for interpreting paleoclimate records, we performed an actualistic study of magnetite alteration in rock weathering in dependence of climatic conditions, in particular mean annual precipitation (MAP). Using basalts as a common rock type, we compared fresh rock and related weathered material at sites with different MAP and different mean annual temperature (MAT). The results show that alteration of magnetite is only slightly stronger in wetter climates, but surprisingly clearly stronger in colder climates at same MAP. The latter is possibly due to micro‐cracks formed through freezing and thawing that opens pathways for moisture and oxygen into particle interiors. Overall, the results suggest that climate‐dependent magnetite alteration during rock weathering in the catchment is unlikely a controlling factor of paleoclimate records. Rock magnetic variability of source rocks will mostly hide these effects. Key Points: Stronger alteration of magnetite during rock weathering in wetter climates is indicated, but is hidden by source rock heterogeneity At equal humidity, magnetite alteration can be stronger in colder climates, possibly favored by frost‐induced micro‐cracks Magnetic records in sediment archives will likely not show humidity‐related magnetite alteration effects acquired during rock weathering